2009
DOI: 10.2166/aqua.2009.021
|View full text |Cite
|
Sign up to set email alerts
|

Rise velocity verification of bubble-floc agglomerates using population balance in the DAF process

Abstract: The dimension of the separation zone in the dissolved air flotation (DAF) process is practically determined by the rise velocity of the bubble-floc agglomerates: flocs attached to several bubbles. To improve the flotation velocity and particle removal efficiency in the DAF process, many researchers have tried to attach as many bubbles as possible to flocs. In this study, the rise velocity of bubble-floc agglomerates, considered to be the most important factor in designing the separation zone of the flotation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
(19 reference statements)
0
10
0
1
Order By: Relevance
“…Com relação às técnicas atualmente empregadas na captura e análise de imagens de flocos e microbolhas de ar formados durante o processo de flotação, tem se verificado que ao longo dos últimos anos ocorreu um aumento significativo no número de pesquisas desenvolvidas, dada a importância que essas partículas exercem sobre a cinética do processo de flotação (BACHE & RASOOL, 2001;RODRIGUES & RUBIO, 2003;MORUZZI, 2005;LEE et al, 2007;HAN et al, 2007;KWAK et al, 2009;SOHN et al, 2009;OLIVEIRA et al, 2010).…”
Section: Introductionunclassified
“…Com relação às técnicas atualmente empregadas na captura e análise de imagens de flocos e microbolhas de ar formados durante o processo de flotação, tem se verificado que ao longo dos últimos anos ocorreu um aumento significativo no número de pesquisas desenvolvidas, dada a importância que essas partículas exercem sobre a cinética do processo de flotação (BACHE & RASOOL, 2001;RODRIGUES & RUBIO, 2003;MORUZZI, 2005;LEE et al, 2007;HAN et al, 2007;KWAK et al, 2009;SOHN et al, 2009;OLIVEIRA et al, 2010).…”
Section: Introductionunclassified
“…To obtain its value, it is tested according to the collision-attachment tendency of the particle on the bubble. A typical value for an inorganic particle such a sa kaolin in the DAF process is 0.3-0.4 [19].…”
Section: Collision Efficiency Using Trajectory Analysismentioning
confidence: 99%
“…Many previous studies (Edzwald 1995;Fultushi et al 1995;Han 2002;Kwak et al 2009) have reported that the most important parameters in the DAF system are the surface characteristics (zeta potential) and the size distribution of both bubble and particle. Particle size as an important parameter in flotation has been the focus of flotation research for decades (Shahbazi et al 2010).…”
Section: Introductionmentioning
confidence: 99%